ANALISIS EFISIENSI BANK PEMBIAYAAN RAKYAT SYARIAH (BPRS) WILAYAH JAWA TENGAH & DIY DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) PERIODE 2016 – 2018 - ayuningtyas, rosida dwi (Fakultas Ekonomi dan Bisnis Islam, 2020)
This study aims to analyze the efficiency level of BPRS in the Central Java and DIY regions during the 2016-2018 period using the Data Envelopment Analysis (DEA) method. This study uses input variables consisting of third party funds, operating expenses and fixed assets, and uses output variables consisting of financing and operating income. This research uses quantitative methods and the data used is secondary data obtained from the financial reports of BPRS for the Central Java and DIY regions.. Based on calculations using the Banxia Frontier Analysis software, of the 33 BPRS that were sampled there were only 6 BPRS which always achieved 100% efficiency levels during 2016-2018, consisting of 2 BPRS in the Central Java region and 4 BPRS in the DIY area, namely PT. BPRS Sukowati Sragen and PT. BPRS Harta Insan Karimah Bahari for the Central Java region, PT. BPRS Madina Mandiri Sejahtera, PT. BPRS Mitra Amal Mulia, PT. BPRS Danagung Syariah and PT. BPRS Mitra Harmoni Yogyakarta for the DIY area. The rest has not yet reached efficiency. This inefficient is caused by a lack of productive financing distribution.